Surface electromyographic activity of the erector spinae and multifidus during arm- and leg-ergometer exercises in young healthy men - Shima, Daichi; Nishimura, Yukihide; Hashizaki, Takamasa; Minoshima, Yuta; Yoshikawa, Tatsuya; Umemoto, Yasunori; Kinoshita, Tokio; Kouda, Ken; Tajima, Fumihiro; Kamijo, Yoshi-Ichiro (Frontiers in Physiology, 2022)
Abstract Objectives. Ergometer exercise was considered a new loading method that can be used for participants who are unable to assume the core strengthening exercise posture commonly used to strengthen the erector spinae and multifidus. This study aimed to investigate with healthy participants whether arm and leg ergometers could be used for core strengthening exercises and whether different exercise sites would affect the results. Methods. The study was conducted with 15 healthy adult male participants aged 20-35 years. The intervention consisted of arm- and leg-ergometer exercises performed by the participants. The exercise protocol consisted of three one-minute sessions (rest, 50W, and 100W), which were measured consecutively. Surface electromyography (sEMG) was measured during the sessions. Maximal voluntary contraction (MVC) of the erector spinae and multifidus was also measured, during which sEMG was measured. The sEMG during ergometer exercise was calculated as a percentage of the MVC. (calculated as % MVC). The root mean square (RMS) was recorded from the sEMG activity. Muscle activity of the erector spinae and multifidus was compared between ergometer exercises and between intensity levels. Heart rate (HR) was recorded by electrocardiogram. Results. In the arm-ergometer exercise, the % MVC values of the erector spinae were 6.3 ± 3.1, 10.9 ± 5.4, and 16.9 ± 8.3% at rest, 50W, and 100W conditions, respectively. The multifidus was 4.6 ± 2.9, 9.2 ± 5.6, and 12.6 ± 7.6% at rest, 50W, and 100W conditions, respectively. The respective % MVC values during the leg-ergometer exercise were 3.8 ± 1.7, 7.2 ± 3.8, and 10.4 ± 4.0% at rest, 50W, and 100W conditions, respectively. Leg-ergometer exercises were 2.6 ± 2.1, 6.9 ± 5.7, and 10.3 ± 6.8% at rest, 50W, and 100W conditions, respectively. The activities of the two muscles increased at comparable levels with increased workload in both types of exercises (P<0.01, each). HR increased with the increased workload and the increase was larger during arm- than leg-ergometer exercises. Conclusion. These results demonstrate that both arm- and leg-ergometer exercises are potentially alternative methods for erector spinae and multifidus training for healthy participants . Further research is needed to target elderly.